2023
DOI: 10.1109/led.2022.3220877
|View full text |Cite
|
Sign up to set email alerts
|

AlScN/GaN HEMTs Grown by Metal-Organic Chemical Vapor Deposition With 8.4 W/mm Output Power and 48 % Power-Added Efficiency at 30 GHz

Abstract: We report on DC and RF measurement results of AlScN/GaN high electron mobility transistors (HEMTs) grown by metal-organic chemical vapor deposition (MOCVD). Comparing the properties with those of a wafer grown with the same MOCVD tool but featuring an Al-GaN barrier, the sheet carrier density (ns) of 1.50 × 10 13 cm −2 measured on the AlScN/GaN wafer is around 60 % higher. This translates to a power density (Pout) of 8.4 W/mm at a frequency of 30 GHz and a drain bias of 30 V. Also, a high power-added efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…SiN x was found to be the ideal passivation layer to prevent oxidation of the AlScN barrier while GaN tends to grow in a 3D-mode on Sc-rich layers. , SiN x passivation is also expected to improve the device performance by the reduction of dispersion, which was recently demonstrated by Tahhan et al Meanwhile, we achieved the first promising results using the novel precursor (MCp) 2 ScCl with increased vapor pressure which are discussed in detail in Streicher et al . We demonstrated AlScN/GaN HEMTs with a saturation drain current density of 1.7 A/mm –1 and a large-signal performance at 30 GHz which reaches a power-added efficiency of 48.9% and an output power of of 8.4 W/mm at a drain-source voltage of 25 and 30 V, respectively . The study presented here was conducted using the standard Sc precursor Cp 3 Sc, obtaining an AlScN barrier layer with a Sc-content of below 10%.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…SiN x was found to be the ideal passivation layer to prevent oxidation of the AlScN barrier while GaN tends to grow in a 3D-mode on Sc-rich layers. , SiN x passivation is also expected to improve the device performance by the reduction of dispersion, which was recently demonstrated by Tahhan et al Meanwhile, we achieved the first promising results using the novel precursor (MCp) 2 ScCl with increased vapor pressure which are discussed in detail in Streicher et al . We demonstrated AlScN/GaN HEMTs with a saturation drain current density of 1.7 A/mm –1 and a large-signal performance at 30 GHz which reaches a power-added efficiency of 48.9% and an output power of of 8.4 W/mm at a drain-source voltage of 25 and 30 V, respectively . The study presented here was conducted using the standard Sc precursor Cp 3 Sc, obtaining an AlScN barrier layer with a Sc-content of below 10%.…”
Section: Introductionmentioning
confidence: 55%
“…24 We demonstrated AlScN/GaN HEMTs with a saturation drain current density of 1.7 A/mm −1 and a large-signal performance at 30 GHz which reaches a power-added efficiency of 48.9% and an output power of of 8.4 W/mm at a drain-source voltage of 25 and 30 V, respectively. 25 The study presented here was conducted using the standard Sc precursor Cp 3 Sc, obtaining an AlScN barrier layer with a Sccontent of below 10%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Very recently, the improvement of material quality as well as 2DEG mobility in ScAlGaN/GaN compared to ScAlN/GaN has been reported [69], which maybe one of the reasons for the performance improvement in ScAl-GaN/GaN HEMT devices. Most recently, Krause et al reported an output power of 8.4 W mm −1 and a power-added efficiency of 48% in MOCVD-grown ScAlN/GaN HEMT devices [202].…”
Section: Hemtsmentioning
confidence: 99%
“…Solid solutions with wurtzite-type crystal structure are one of the newest material classes to have been confirmed as been demonstrated in the last years, targeting either HEMT or RF-filters, no demonstration of ferroelectricity has been reported so far. [9][10][11][12] In this work, we demonstrate for the first time that single crystalline Al 0.85 Sc 0.15 N films grown on GaN templates by MOCVD are indeed ferroelectric. Apart from standard electrical characterization to deduce the displacement current originating from the polarization inversion and to confirm a particularly high coercive field of 5.5 MV cm −1 , we focus on high resolution scanning transmission electron microscopy (STEM) for the imaging of the atomic structure.…”
Section: Introductionmentioning
confidence: 99%